Rekayasa Sosial dalam Fenomena Save LGBT - Gunawan Saleh; Muhammad Arif (Jurnal Komunikasi Global, 2017)
This research will explore the existence of social engineering agenda in phenomenon SAVE LGBT. This phenomenon is actually a classical social problem. Due to the fact that homosexual and lesbian problems existed in the days of prophets long before humans became familiar with modern civilization Lately in the 20th century the development of civilization is increasingly alarming with the emergence of the idea of freedom of work, expression, and even freedom in terms of sexuality in the name of Human Rights (HAM). A group of people tried with various attempts to legalize themselves using the Human Rights Act. This research will discuss social engineering in the phenomenon of SAVE LGBT. It uses qualitative approach by conducting in-depth interviews with eight informants. The results show that social engineering is clearly visible where a group of people trying to voice SAVE LGBT with the meaning of their behavior must get the same protection. But in fact, SAVE said more to give the right to life and not discriminated and to give them help to return to its nature. Then there is a mistake in understanding the Law on Human Rights, which is only a small group who voiced rights as human beings but they do not see the right to life of most people who reject the LGBT behavior.